Boundary stabilization of systems of high order PDEs arising from flexible robotics. Issue 2 (2020) - Cristofaro, A.; Ferrante, F.
Abstract: Stabilization of a system of coupled PDEs of the fourth-order by means of boundary control is investigated. The considered setup arises from the classical Euler-Bernoulli beam model, and constitutes a generalization of flexible mechanical systems. A linear feedback controller is proposed, and using an abstract formulation based on operator semigroup theory, we are able to prove the well-posedness and the stability of the closed-loop system. The performances of the proposed controller are illustrated by means of numerical simulations.